Pembelajaran Sejarah Islam dan Kearifan Lokal - Khazanah Fauziah, Khotimah; Fauzan, Pepen Irfan (Al Mudzakarah, 2024)
The monotonous process of learning history is one of the factors in low historical literacy. This study discusses how to improve Islamic historical literacy skills with the Sakali Wayang Motekar (MASAGI) learning method based on local wisdom amid the onslaught of learning methods oriented to western culture which is considered practical and efficient. This research uses research and development (R&D) methods using six development steps, namely potential problem stages, data collection, product design, product validation, product revision and products. However, because the research is tailored to existing needs, the research is limited to tests, interviews, and other supporting notes with a qualitative approach. The results showed that the fulfillment of the historical literacy benchmark dimension conceptualized by Mapossa and Wasserman was successfully fulfilled by the sakali wayang motekar (MASAGI) method and contributed to increasing the historical literacy ability of students quite satisfactorily with dimensions with three dimensions fulfilled properly, the source work dimension only uses two sub-dimensions, namely source search and explanation, other sub-dimensions are considered unusable for students class VIII but conducted by SKI teachers using the teacher's eclectic rights.